PENGARUH MODEL PEMBELAJARAN SPONTANEOUS GROUP DISCUSSION (SGD) PADA MATERI SISTEM EKSKRESI TERHADAP HASIL BELAJAR SISWA KELAS VIII SMPN 1 BATANG KAB. JENEPONTO - Arpina, Pipi; Taufiq, Ainul Uyuni; Ismail, Wahyuni (Al-AHYA: Jurnal Pendidikan Biologi, 2025)
This study aims to analyze the effect of the Spontaneous Group Discussion (SGD) learning model on students’ learning outcomes in the topic of the excretory system. A quantitative approach was employed using a quasi-experimental design with a nonequivalent control group. The research sample consisted of two eighth-grade classes at SMPN 1 Batang, Jeneponto Regency, selected through purposive sampling. Each class comprised 35 students, assigned as the experimental and control groups. Data were collected using a learning outcomes test and analyzed using an independent samples t-test. The results showed that the mean posttest score of the experimental class was 76.14, which was higher than that of the control class, which obtained a mean score of 67.57. The statistical analysis yielded a Sig. (2-tailed) value of 0.000 < 0.05, indicating that the Spontaneous Group Discussion (SGD) learning model had a significant effect on improving students’ learning outcomes in the topic of the excretory system.